Hydrogen peroxide concentration as an indicator of cyanobacterial response to diurnal variation in light intensity - Takashi Asaeda; Mizanur Rahman; Junichi Akimoto; Akio Nohara; Fumiko Imamura (Scientific Reports)
Abstract We measured diurnal variations in oxidative stress conditions of cyanobacteria utilizing field observations and laboratory experiments in order to evaluate photoinhibition effects. On clear summer days, transparent bottles filled with surface water were set up at several depths and were collected every three hours together with the measurement of the photosynthetically active radiation (PAR). In the laboratory experiment, two cyanobacterial species were exposed to gradually increasing and then decreasing light intensities. The samples were analyzed with the PAR-induced (H2O2), along with the total hydrogen peroxide concentrations (total H2O2), the catalase activities (CAT), OD730, protein (Protein), and chlorophyll a (Chl a) contents, and so on. Protein was significantly proportionate with OD730 and Chl a, and was used as an indicator of cell biomass. Increasing PAR, H2O2 concentration increased proportionately with the PAR intensity. Then, an oxidative stress indicator in a cell, H2O2/Protein is given by the PAR divided by cell volume, evaluated by Protein. CAT activity in a cell, far largest among antioxidant activities, solely followed total H2O2/Protein. The prediction model for H2O2/Protein was developed with the sufficient agreement with the experimental and field observation results. The model elucidated that the maximum H2O2/Protein in a day was larger with lower cell density even at the water surface, indicating that the higher photoinhibition was imposed at low density, in addition to the lower attenuation of PAR. These results indicate that H2O2/Protein is an effective biomarker to indicate the stress level of cyanobacteria; the observed levels of H2O2 to freshwater may prove useful in designing the criteria for cyanobacteria management.